TINGKAT LITERASI KESEHATAN DAN HUBUNGANNYA DENGAN DIABETICS SELF MANAGEMENT PADA KLIEN DENGAN DIABETES MELLITUS TYPE 2 - Sari, Yunita; Sari, Cucuk Kunang (Jurnal Medikes (Media Informasi Kesehatan), 2023)
Diabetes Mellitus (DM) is a chronic disease that is gradually contributing as a major cause of mortality and morbidity throughout the world. The number of diabetes cases increases every year and it is predicted that in 2030 there will be 578 million cases of DM and as many as 700 million in 2045. To minimize and prevent complications in DM sufferers, clients need understanding and ability to manage their disease. Health literacy is an important factor for clients with chronic illnesses, including DM, to support clients’ ability to carry out daily care. The aim of this study was to identify the relationship between the level of health literacy and diabetic self-management (DSM) of type 2 DM clients. This study used a cross-sectional study design using a sample of 60 type 2 DM clients. The variables in this study were the level of health literacy and diabetes self-management. management. From the results of the correlation test using the chi square test, correlation results were obtained which showed that there was a significant relationship between the level of health literacy and the DSM of type 2 DM clients (p value 0.001). This research can be a basis for determining appropriate interventions as an effort to improve the literacy skills of DM clients.